PERANCANGAN TATA KELOLA TEKNOLOGI INFORMASI PADA MA DARUSSALAM PANGKALPINANG MENGGUNAKAN FRAMEWORK COBIT 2019 - Faruq Vista, Umar; Rapina (Information Technology Education Department, 2024)
Both now and in the future, the governance of information technology services is evolving at a rapid pace. Information technology is essential to the performance of organizations, institutions and companies in the modern era. In addition, information technology can improve the efficiency and effectiveness of decision-making. Information technology services are used in all fields, especially in education. For example, MA Darussalam Pangkalpinang has used information technology to support academic and business activities, but it has not been audited. The school's information system has not been integrated and cannot support business processes. Based on the Control Objectives for Information and Related Technology (COBIT) 2019 framework, this research investigates the design of information technology (IT) governance at Madrasah Aliyah (MA) Darussalam Pangkalpinang. This research uses a qualitative approach, where data is collected through interviews with MA Darussalam Pangkalpinang stakeholders and literature study. This research reviews the existing information systems and uses the COBIT 2019 framework to create an IT management plan for MA Darussalam Pangkalpinang. This plan will help andsupport business processes to run in accordance with regulations and requirements, as well as improve the integration and efficiency of school information systems.